Spatio-temporal connectivity and dispersal seasonal patterns in the Adriatic Sea using a retention clock approach - Nadal, Irene; Picciulin, Marta; Falcieri, Francesco M.; García-Lafuente, Jesús; Sammartino, Simone; Ghezzo, Michol (Frontiers in Marine Science, 2024)
Hydrodynamic features are crucial in determining the dispersal and connectivity of fish populations, particularly in highly energetic areas influenced by currents, river flow, and meteorologically induced fluctuations. Understanding how species interact with these physical processes is essential for managing vulnerable populations and identifying areas that require effective conservation efforts. This study examines the hydrodynamics that regulate connectivity in the Adriatic Sea, a shallow and semi-enclosed basin that is widely recognized as one of the most important areas in the Mediterranean Sea for protection. The numerical tool used in this study is a high-resolution hydrodynamic model coupled with a lagrangian tracking module. Lagrangian particles, representing eggs and larvae with typical biological characteristics of generic marine organisms inhabiting the region, are released throughout the basin at different times during a test year to identify the most likely pathways of individual dispersal. The temporal component of connectivity is highlighted by using a previously developed retention clock matrix over different pelagic larval durations. Seasonality is a crucial factor in dispersion, with greater fluctuations and reduced efficiency during winter compared to summer. The potential implications of the results for the improved assessment and management of highly valued marine species in the basin are discussed.